2021
DOI: 10.1097/01.naj.0000742504.44428.c9
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Physiological Monitoring Improves Patient Outcomes

Abstract: Background: General patient acuity is increasing in the United States, with more patients having multiple comorbidities and acute-on-chronic conditions. Hospitalizations may also be complicated by serious adverse events, often unrelated to the admitting medical diagnosis. In our facility, the late detection of patient deterioration on general medical units often resulted in increased length of stay (LOS) in the ICU and poor patient outcomes. Purpose: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…38 Multiple subsequent studies investigating a variety of continuous monitoring modalities have also found decreases in RRTs and ICU transfers, and in 1 study decreases in cardiac arrests and in-hospital mortality were also noted. 39–44 Meta-analyses have shown similar results, including reductions in ICU transfers but not in mortality. 45,46 However, most of these studies lacked detailed information about the larger rescue system infrastructure and about how monitoring is operationalized and built into clinical workflows.…”
Section: Pro Position: Universal Continuous Respiratory Monitoring Of...mentioning
confidence: 82%
“…38 Multiple subsequent studies investigating a variety of continuous monitoring modalities have also found decreases in RRTs and ICU transfers, and in 1 study decreases in cardiac arrests and in-hospital mortality were also noted. 39–44 Meta-analyses have shown similar results, including reductions in ICU transfers but not in mortality. 45,46 However, most of these studies lacked detailed information about the larger rescue system infrastructure and about how monitoring is operationalized and built into clinical workflows.…”
Section: Pro Position: Universal Continuous Respiratory Monitoring Of...mentioning
confidence: 82%
“…Until reliable sensing and preprocessing techniques are available for all relevant parameters, it would be of interest to develop ways to optimally combine sensor and nurse measurements in care routines. Various commercially available systems for wireless or automatic patient monitoring already support or are used for the calculation of complete EWS every few hours [ 12 , 41 ], often after verification of valid measurement values and manual insertion of parameters that cannot yet be measured by the system, such as blood pressure or consciousness. Following this approach, Weenk et al [ 23 ] performed a study that included patients on wards, where an EWS was calculated every 30 minutes using 2 different wireless vital sign sensor systems and complementary nurse measurements.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results of at least seven large (>1000 patients) studies reporting significant postoperative clinical outcome benefits after the implementation of continuous monitoring on hospital wards. 17 , 18 , 19 , 20 , 21 , 22 , 23 Five of these studies 17 , 19 , 21 , 22 , 23 reported a significant decrease in the number of RRT interventions after the implementation of continuous monitoring of heart rate, respiratory rate, blood pressure, and/or oxygenation saturation on regular wards. Two studies 17 , 23 reported a significant decrease in the number of ICU transfers.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 , 15 By enabling the early detection of clinical trajectories, 16 continuous monitoring of vital signs may help to decrease severe adverse events requiring rescue interventions, ICU admissions, and deaths. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 …”
mentioning
confidence: 99%